RETRACTED ARTICLE: Linc-ROR facilitates progression and angiogenesis of hepatocellular carcinoma by modulating DEPDC1 expression - Chuan Tian; Mubalake Abudoureyimu; Xinrong Lin; Xiaoyuan Chu; Rui Wang (Cell Death and Disease)
Abstract Linc-ROR have been well-demonstrated to play important roles in cancer progression and angiogenesis. However, the underlying oncogenic mechanism of Linc-ROR in hepatocellular carcinoma is poorly understood. In this study, we demonstrate that Linc-ROR plays an oncogenic role in part through its positive regulation of DEPDC1 expression. Mechanistically, Linc-ROR acts as competing endogenous RNA to stabilize DEPDC1 mRNA and regulates DEPDC1 mRNA stability by binding HNRNPK. Thus, these findings suggest that function of Linc-ROR-mediated DEPDC1 could predispose hepatocellular carcinoma patients to progression and angiogenesis, and may serve as a potential target for anticancer therapies.